Impact of landfill waste on human health - Архіпова, Г.І.; Галушка, Ю.О. (Proceedings of National Aviation University (archive), 2009)
Concidered is the impact of dampings solid wastes, which are situated near the populated areas, to the health of people and haveanylazed foreign investigations in this direction.